Factors related to positive airway pressure adherence in patients with obstructive sleep apnea at King Chulalongkorn Memorial Hospital - Pithathitikul, Piraya; Lalitanantponga, Decha; Thienwiwatnukul, Krittapas; Srisawart, Puntarik (Chulalongkorn Medical Journal, 2023)
Background: Positive airway pressure (PAPs) is a standard and efficacious treatment for obstructive sleep apnea (OSA). Poor adherence could lead to impaired daytime performance, increasing risk of traffic accidents, hypertension, cardiovascular events, and neuropsychological disturbances. Previous studies reported rates and factors influencing PAPs adherence, but the data in Thailand was still lacking. Objectives: To investigate the rate of PAPs adherence, the prevalence of depressive and anxiety symptoms, and the factors associated with PAPs adherence among patients with OSA. Methods: This is a cross-sectional descriptive study that was conducted during June 2021 to September 2022. The data was collected from patients with ages 18 years old who were diagnosed with OSA, suggested by physician to use PAPs for treatment, and currently being followed-up at King Chulalongkorn Memorial Hospital (KCMH). The questionnaires developed by the investigator were used to assess demographic and clinical data, factors associated with PAPs adherence and rate of PAPs adherence. Thai Hospital Anxiety and Depression Scale (HADS) was used to assess the prevalence of depressive and anxiety symptoms. Results: A total of 115 patients consented to participate in this study. Forty-eigth of the subjects (41.7%) met the adherence criteria in this study. The prevalence of depressive and anxiety symptoms was 1.7% and 3.5%, respectively. The mean depressive scores in the adherence group were statistically less than those in the non-adherence group (P = 0.046), but there were no significant different in mean anxiety scores between the two groups (P = 0.308). Significant associated factors related to PAPs adherence were income, improving of daytime sleepiness, usage of OSA impacted medication, number of OSA impacted medication using, and feeling difficulty to breath while using the PAPs machine. Multivariate analysis demonstrated a significant association between lower income (less than 30,000 Thai baht per month) and the feeling of difficulty to breath while using the PAPs machine with the non-adherence to PAPs using while other covariate factors were controlled. Conclusion: The prevalence of depression and anxiety was lower than other previous studies. Income, improving of daytime sleepiness, usage of and number of OSA impacted medications, and feeling difficulty to breath while using the PAPs machine were significant factors associated with PAPs adherence. Income less than 30,000 Baht per month and reported difficulty to breath during PAPs treatment could predict future nonadherence to PAPs treatment.